Safety and efficacy of flecainide associated with beta-blockers in arrhythmogenic right ventricular cardiomyopathy. Issue 2 (30th August 2021) - Rolland, Thomas; Badenco, Nicolas; Maupain, Carole; Duthoit, Guillaume; Waintraub, Xavier; Laredo, Mikael; Himbert, Caroline; Frank, Robert; Hidden-Lucet, Francoise; Gandjbakhch, Estelle
Abstract: Aims: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited cardiomyopathy associated with a high risk of ventricular arrhythmia (VA). Current guidelines recommend beta-blockers as first-line medical therapy and if ineffective, sotalol or amiodarone. We describe our experience, as a tertiary centre for ARVC, with the effectiveness and tolerance of flecainide in addition to beta-blockers to prevent VA in ARVC. Methods and results: We retrospectively included 100 consecutive ARVC patients who received flecainide with beta-blockers between May 1999 and November 2017. Treatment persistence and related side effects were assessed, as was VA-free survival on treatment, 24-h Holter monitoring and programmed ventricular stimulation (PVS) off- and on-treatment. Tolerance was good, with 10% flecainide discontinuations (lack of efficacy in six, atrial fibrillation in one, and side effects in three). No Brugada-induced electrocardiography pattern on flecainide or haemodynamic impairment was reported. Premature ventricular contraction burden at 24-h Holter monitoring was significantly decreased under treatment [median 415 (interquartile range, IQR 97–730) vs. 2370 (1572–3400) at baseline, P < 0.0001, n = 46]. Among the 33 patients with PVS under treatment, PVS was positive in 40% on-treatment vs. 94% off-treatment ( P < 0.001). During a median follow-up of 47 months (IQR 23–73), 22 patients presented sustained VA on treatment, corresponding to an event rate of 5% [95% confidence interval (CI) (0.6–9)] at 1 year and 25% [95% CI (14–35)] at 5 years under treatment. No patient died. Conclusion: This study suggests that flecainide and beta-blockers association is complementary to implantable cardioverter-defibrillator and catheter ablation and is safe for treating persistent symptomatic VA in patients with ARVC.